Ideology-Based Sharia Marketing Strategy in Increasing Consumer Preference for Nucless Drinking Water in Ponorogo - Diva Hayu Regita Pramesti; Nizar Haris Masruri (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
The bottled drinking water (AMDK) industry is currently increasingly competitive, dominated by well-known major brands. NUCless is a new product that offers high quality, affordable prices, and upholds the values of Nahdlatul Ulama (NU), which aims to empower the community economically. However, consumer preference for NUCless in Ponorogo remains low, even though the majority of the community is NU members. This study aims to analyze ideology-based sharia marketing strategies in increasing consumer preference and their impact. The method used is a qualitative field approach. Data were collected through interviews and documentation with six informants, including NUCless distributors and NU members. The results of this study indicate that NUCless distributors have implemented three sharia marketing paradigms: mind share, market share, and heart share, by integrating NU ideological values. However, this strategy has not had a significant impact on increasing consumer preference, marked by stagnant sales. Contributing factors include cultural, social, personal, and psychological factors. The conclusion of this study indicates that ideology-based marketing strategies alone are not effective enough to increase consumer preference. A more creative and relevant Islamic marketing approach to current consumer behavior is needed so that NUCless can compete and grow sustainably amidst tight market competition.